Pengaruh Kualitas Pelayanan Dan Infrastructure Terhadap Loyalitas Pelanggan Dengan Tingkat Kepuasan Pelanggan Sebagai Variabel Intervening Di Cuci Mobil Ronggolawe Boyolali - Sasongko, Pamor Cokro; , Dr. Anton Agus Setiawan, SE, M.Si; , Drs. M. Farid Wajdi, M.M., Pd. D (2017)
This study aimed to know and demonstrate empirically the effect of tangible, reliability, responsiveness, assurance, empathy, and infrastructure variables to customer satisfaction, the effect of tangible, reliability, responsiveness, assurance, empathy, and infrastructure variabels to customer loyalty, and the effect of customer satisfaction variable to customer loyalty in a Ronggolawe car wash of Boyolali. This study is a quantitative research. The sample in this study are 100 customers of Ronggolawe car wash of Boyolali using saturation sampling technique. Data was collected by questionnaire. Data analysis technique using path analysis. The results of this study indicate that partially and simultaneously variables of tangibles, assurance, empathy, reliabilty, responsivenees, and infrastructure have effect on customer satisfaction and also partially and simultaneously variables of tangibles, assurance, empathy, reliabilty, responsivenees, infrastructure and customer satisfaction have effect on customer loyalty in the Ronggolawe car wash of Boyolali.